What is yopará? (Observations on paraguayan Spanish) - A. Sadikov (Ибероамериканские тетради)
The article purports to summarize and rethink a considerable amount of facts collected by various researchers who studied the linguistic situation and the interplay of two languages, Spanish and Guarani, in modern Paraguay. Having revised a number facts pertaining to different levels of the language system, the author arrives at the conclusion that the linguistic phenomenon called yopará is emerging as a new language in the full sense of this word, its mixed origin notwithstanding, a real future national language now taking shape.